Revealing phylogenetic relationships of Cyprinidae based on DNA barcoding in Merangin Jambi Geopark, Indonesia - TEDJO SUKMONO; TEJA KASWARI; PRADITA EKO PRASETYO UTOMO; TIA WULANDARI; SARWO EDY WIBOWO; FEBRINA ROLIN; NURJIRANA NURJIRANA (Society for Indonesian Biodiversity, 2026)
Abstract. Sukmono T, Kaswari T, Utomo PEP, Wulandari T, Wibowo SE, Rolin F, Nurjirana. 2026. Revealing phylogenetic relationships of Cyprinidae based on DNA barcoding in Merangin Jambi Geopark, Indonesia. Biodiversitas 27 (3): d270317. https://doi.org/10.13057/biodiv/d270317. Cyprinidae, a dominant freshwater fish family, plays a crucial role in biodiversity and ecosystem functioning. The Merangin Jambi Geopark, under evaluation for the UNESCO Global Geopark Network, hosts a rich freshwater fish fauna, but morphological identification is challenging due to overlapping characters. This study employed DNA barcoding of the mitochondrial COI gene to identify species and investigate phylogenetic relationships of Cyprinidae. A total of 26 individuals representing 14 species across 10 genera were analyzed. The Cytochrome C Oxidase subunit I (COI) gene ( 650 bp) was amplified and sequenced. Sequence analysis was performed using Basic Local Alignment Search Tool (BLAST), and a phylogenetic tree was constructed in MEGA 12. Sequence similarity ranged from 88.11% to 99.56%, with most species exceeding 96% identity, indicating strong intraspecific homogeneity and clear intergeneric divergence. Genetic distances ranged from 0.000 to 0.179, reflecting population stability in species such as Barbodes lateristriga and Rasbora spilotaenia, and high divergence in species like Luciosoma spilopleura and Epalzeorhynchos kalopterus. Phylogenetic reconstruction revealed two major clades, with samples clustering consistently with GenBank reference sequences, confirming accurate species identification and taxonomic placement. Based on IUCN status, most species were categorized as Least Concern, though several were Data Deficient or Not Evaluated, highlighting the need for local conservation attention. These findings demonstrate that DNA barcoding effectively complements morphological taxonomy and provides a robust framework for biodiversity monitoring. Furthermore, the study contributes to local conservation by informing habitat protection, species management, and sustainable freshwater resource utilization in the Merangin Jambi Geopark.